Membangun Brand Inklusif: Strategi Branding dan Pemasaran untuk Produk Usaha Mikro Kecil Menengah Difabel - Eko Saputra, Priangga; Dhewi, Titis Shinta; Agus P, Afwan Hariri; Muhammad, Naufal Dzakwana; Dinata, Daffa Hikary Sukma (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
This Community Partnership Program was implemented to enhance the capacity of micro, small, and medium enterprise (MSME) actors with disabilities in Banyuwangi in the areas of branding and digital marketing. The program was specifically designed to address challenges of accessibility, social stigma, and limited access to technology faced by MSMEs with disabilities in building competitive brands. The activities were carried out through three stages: preparation stage in the form of coordination and socialization, implementation of training using modules (basic branding with an inclusive approach, visual design based on accessible technology, and adaptive digital marketing), and continuous evaluation. The approach used integrates digital accessibility principles and branding strategies that utilize the uniqueness of disability identity as product differentiation. Quantitative achievements showed significant improvements in branding comprehension (73%), brand name development (85%), logo creation (80%), design technology mastery (75%), and digital marketing planning (90%). Qualitative achievements include participants' success in forming brand identities that utilize disability perspectives as unique value, increased self-confidence, motivation, and the ability to transform disability identity into competitive advantage. The program demonstrates the effectiveness of inclusive approaches in strengthening the competitiveness of MSMEs with disabilities sustainably.